Regulador de tensão de sistema de compensação de reativos em microgeração de energia - Biernaski, Elias Eli (2021)
This paper presents an alternative of tension regulation on a self-excited asynchronous micro-generator, through the use of an Arduino UNO linked to a static reactive power compensator. In this context, a study about induction generators and the automatization of the reactive power compensator is done. During the practical development of the paper the test bench available on the C-002 lab at UTFPR Campus Curitiba/CT is presented. The implementation of the automatization of the reactive control is developed through an Arduino UNO plate, along with an AC 0 a 250V – ZMPT101B tension sensor and a convertor from PWM to tension 0 to 10Vdc – Model CPT10. Primarily, the Arduino UNO microcontroller accomplishes a sequence of measurements and initiates the firmware, after that stage, the output signal of the Arduino plate is converted into an output signal Vdc, which is responsible for powering the compensator and normalizing the tension in the generator’s terminals. A few tests are done with the objective of checking the behavior of the developed regulator after the insertion and removal of the load. Lastly, a few conclusions about the development stages of the project are presented.